Beyond Liquidity: New Uses for Developing Asia's Foreign Exchange Reserves - Donghyun Park (Asian Development Bank (ADB), 2007)
Dong Hyun Park finds evidence strongly supportive of popular opinion that developing Asia should manage its foreign exchange reserves more actively. The analysis indicates that, contrary to popular opinion, the region's reserves are not a free fiscal asset but the income from investing them represents a fiscal dividend for the region's governments. This and other factors suggest that the first-best use of the region's reserves is to invest them abroad to maximize risk-adjusted returns. The resulting expansion of fiscal space will help the region's governments tackle the huge long-term developmental challenges still facing the region
hdl:11540/1867
Keywords: 330; Währungsreserven; Asien